Modulation of Multidrug Resistance Gene Expression by Coumarin Derivatives in Human Leukemic Cells. (13th December 2017) - Kubrak, Tomasz; Bogucka-Kocka, Anna; Komsta, Łukasz; Załuski, Daniel; Bogucki, Jacek; Galkowski, Dariusz; Kaczmarczyk, Robert; Feldo, Marcin; Cioch, Maria; Kocki, Janusz
Abstract : The presence of multidrug resistance (MDR) in tumor cells is considered as the major cause of failure of cancer chemotherapy. The mechanism responsible for the phenomenon of multidrug resistance is explained, among others, as overexpression of membrane transporters primarily from the ABC family which actively remove cytostatics from the tumor cell. The effect of 20 coumarin derivatives on the cytotoxicity and expression of MDR1, MRP1, BCRP, and LRP genes (encoding proteins responsible for multidrug resistance) in cancer cells was analyzed in the study. The aim of this research included determination of IC10 and IC50 values of selected coumarin derivatives in the presence and absence of mitoxantrone in leukemia cells and analysis of changes in the expression of genes involved in multidrug resistance: MDR1, MRP, LRP, and BCRP after 24-hour exposure of the investigated cell lines to selected coumarins in the presence and absence of mitoxantrone in IC10 and IC50 concentrations. The designed research was conducted on 5 cell lines derived from the human hematopoietic system: CCRF/CEM, CEM/C1, HL-60, HL-60/MX1, and HL-60/MX2. Cell lines CEM/C1, HL-60/MX1, and HL-60/MX2 exhibit a multidrug resistance phenotype.